2000
DOI: 10.1111/j.1469-7793.2000.00119.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinant for run‐down of L‐type Ca2+ channels localized in the carboxyl terminus of the α1C subunit

Abstract: The role of the sequence 1572‐1651 in the C‐terminal tail of the α1C subunit in run‐down of Ca2+ channels was studied by comparing functional properties of the conventional α1C,77 channel with those of three isoforms carrying alterations in this motif. The pore‐forming α1C subunits were co‐expressed with α2δ and β2a subunits in HEK‐tsA201 cells, a subclone of the human embryonic kidney cell line, and studied by whole‐cell and single‐channel patch‐clamp techniques. Replacement of amino acids 1572‐1651 in α1C,77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 56 publications
(80 reference statements)
1
20
1
Order By: Relevance
“…In control cells transfected with Ca v 1.3 LVGCCs (n ϭ 4) in which no drug was applied, the average percentage current remaining 2, 5, and 10 min from the start of recording was 71 Ϯ 11, 57 Ϯ 13, and 42 Ϯ 9%, respectively. This extent of rundown was similar to that of Ca v 1.2 LVGCCs in this study and as reported previously (Kepplinger et al, 2000). There was no apparent correlation between the extent of rundown in different cells and drug concentrationresponse, suggesting that the mechanisms causing the rundown phenomenon were not a significant factor in modifying L-VGCC inhibition by GABA A R modulators.…”
Section: Functional Characterization Of Recombinant L-vgccssupporting
confidence: 90%
“…In control cells transfected with Ca v 1.3 LVGCCs (n ϭ 4) in which no drug was applied, the average percentage current remaining 2, 5, and 10 min from the start of recording was 71 Ϯ 11, 57 Ϯ 13, and 42 Ϯ 9%, respectively. This extent of rundown was similar to that of Ca v 1.2 LVGCCs in this study and as reported previously (Kepplinger et al, 2000). There was no apparent correlation between the extent of rundown in different cells and drug concentrationresponse, suggesting that the mechanisms causing the rundown phenomenon were not a significant factor in modifying L-VGCC inhibition by GABA A R modulators.…”
Section: Functional Characterization Of Recombinant L-vgccssupporting
confidence: 90%
“…Replacements in the cytoplasmic 80-amino acid segment leading to ␣ 1C,86 , ␣ 1C,77L , and ␣ 1C,77K variants affected voltage sensors for activation and inactivation (Soldatov et al, 1997(Soldatov et al, , 1998a, and reduced open probability and single channel conductance (Kepplinger et al, 2000b) thus suggesting that both Ca 2ϩ -sensing domains interact with a pore jpet.aspetjournals.org region and affect the voltage-gating mechanism of the channel. Combined disruption of motifs L and K in ␣ 1C,86 completely eliminated the characteristic run-down property of the channel (Kepplinger et al, 2000a). This region may involve determinants for the rescue effect of calpastatin (Romanin et al, 1991).…”
Section: ؉ Sensors Of the Ca 2؉ Channelmentioning
confidence: 94%
“…In these studies, the drug induced a small, approximately 20%, maximal reduction of basal I Ca,L , and the effect was increased to approximately 30% when the myocytes were isolated from failing hearts (29,53). Surprisingly, the effects of BRL37344 persisted after washout of the drug, which is a concern when considering that I Ca,L is subjected to substantial spontaneous rundown in mammalian cardiomyocytes (55,56). However, the inhibitory effects of BRL37344 were attenuated by preincubation of the cells with the NOS inhibitor N G -nitrol-arginine methyl ester (L-NAME) (50,53) or after treatment of the myocytes with Bordetella pertussis toxin (53), which is consistent with earlier findings that a β 3 -AR signaling cascade involved G i/o protein and NOS3 activation (8,16,17).…”
Section: Figurementioning
confidence: 98%